B-cell-depleted patients with persistent SARS-CoV-2 infection: combination therapy or monotherapy? A real-world experience - Alessandra D’Abramo; Serena Vita; Alessia Beccacece; Assunta Navarra; Raffaella Pisapia; Francesco Maria Fusco; Giulia Matusali; Enrico Girardi; Fabrizio Maggi; Delia Goletti; Emanuele Nicastri; ImmunoCOVID team; et al. (Frontiers in Medicine, 2024)
ObjectivesThe aim of the study was to describe a cohort of B-cell-depleted immunocompromised (IC) patients with prolonged or relapsing COVID-19 treated with monotherapy or combination therapy.MethodsThis is a multicenter observational retrospective study conducted on IC patients consecutively hospitalized with a prolonged or relapsing SARS-CoV-2 infection from November 2020 to January 2023. IC COVID-19 subjects were stratified according to the monotherapy or combination anti-SARS-CoV-2 therapy received.ResultsEighty-eight patients were enrolled, 19 under monotherapy and 69 under combination therapy. The study population had a history of immunosuppression (median of 2 B-cells/mm3, IQR 1–24 cells), and residual hypogammaglobulinemia was observed in 55 patients. A reduced length of hospitalization and time to negative SARS-CoV-2 molecular nasopharyngeal swab (NPS) in the combination versus monotherapy group was observed. In the univariable and multivariable analyses, the percentage change in the rate of days to NPS negativity showed a significant reduction in patients receiving combination therapy compared to those receiving monotherapy.ConclusionIn IC persistent COVID-19 patients, it is essential to explore new therapeutic strategies such as combination multi-target therapy (antiviral or double antiviral plus antibody-based therapies) to avoid persistent viral shedding and/or severe SARS-CoV-2 infection.